1994
DOI: 10.1515/cclm.1994.32.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tissue Factor Pathway Inhibitor in Human Synovial Cells and Chondrocytes Makes Joints the Predilected Site of Bleeding in Haemophiliacs

Abstract: Summary:The synthesis of tissue factor pathway inhibitor (TFPI) was investigated in cloned human synovial cells and human chondrocytes. TFPI-specific DNA transcription products of these cells were isolated, and a full-length cDNA of about 1000 base pairs was amplified by reverse transcription and polymerase chain reaction. The amplified DNA was cloned into the vector pUC 18. The TFPI coding sequence was confirmed by double stranded sequencing and was identical with that previously published for human TFPI codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The increased factor pathway inhibitor is mainly synthesized by vascu-tissue factor pathway inhibitor activity suggested that lar endothelium, where it is bound to heparan sulphate this inhibitor is involved in the post-heparin anticoaguor glycosaminoglycans (6,7), and by other cells, e. g. lant effect following heparin administration. A heparin megakaryocytes and chondrocytes (8). There are three binding site C-terminal from domain 53 has been posintravascular pools of tissue factor pathway inhibitor, in tulated as a mediator of heparin-induced tissue factor pathway inhibitor release from the cell surface (15).…”
Section: Introductionmentioning
confidence: 99%
“…The increased factor pathway inhibitor is mainly synthesized by vascu-tissue factor pathway inhibitor activity suggested that lar endothelium, where it is bound to heparan sulphate this inhibitor is involved in the post-heparin anticoaguor glycosaminoglycans (6,7), and by other cells, e. g. lant effect following heparin administration. A heparin megakaryocytes and chondrocytes (8). There are three binding site C-terminal from domain 53 has been posintravascular pools of tissue factor pathway inhibitor, in tulated as a mediator of heparin-induced tissue factor pathway inhibitor release from the cell surface (15).…”
Section: Introductionmentioning
confidence: 99%
“…Among other cell types tissue factor pathway inhibitor has been shown to be expressed by endothelial cells (17,18), megakaryocytes, chondrocytes and synovial cells (19,20). The extrinsic pathway is initiated by the tissue factor/factor VII complex, which is inhibited by tissue factor pathway inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…2.5 % are found in thrombocytes, which can be released through thrombin stimulation [25]. It is known that megakaryocytes [26], monocytes [27,28], HepG2 cells [29,30,31], and chondrocytes [32] also produce TFPI. The synthesis of TFPI in human synovial cells and human chondrocytes seems to be part of an important regulation process in the synovial system, which maintains a balance between fibrinolytic and clotting reactions during minimal bleeding and avoids inadequate fibrin deposition on the cartilage surface of the joint.…”
Section: Sources Of Tfpimentioning
confidence: 99%
“…In haemophiliacs, factor Xa generation depends exclusively on the factor Vila/tissue factor pathway, since factor VIII or factor IX are deficient. Therefore, the presence of TFPI in the synovial system would seem to be the reason why joints are.the predilected sites of bleeding in patients with haemophilia [32].…”
Section: Sources Of Tfpimentioning
confidence: 99%